SUMOylation is not a prerequisite for HSF1’s role in stress protection and transactivation - Miroslav Bardelcik; Oliver Simoncik; Kristina Bednarova; Ondrej Bonczek; Borivoj Vojtesek; Petr Muller (Scientific Reports)
Abstract Targeting tumor proteostasis has emerged as a promising strategy in anticancer therapy, particularly through Hsp90 inhibition, which has shown clinical potential. However, the efficacy of Hsp90 inhibitors is limited by the activation of HSF1, a master regulator of the heat shock response (HSR), which mitigates proteotoxic stress by inducing protective chaperones. To address this limitation, we investigated the role of HSF1 SUMOylation in modulating its activity and its impact on Hsp90 inhibitor efficacy. We generated HSF1 mutants with lysine-to-arginine substitutions at five SUMOylation sites and studied their function in H1299 lung carcinoma cells with HSF1/HSF2 knockout, which lack a functional HSR. Unexpectedly, these mutants retained full transcriptional activity during the early phase of the heat shock response, mimicking the initial stress response of wild-type HSF1. SUMOylation inhibition using Subasumstat also led to altered nuclear stress bodies morphology but did not impair Hsp70 induction or enhance Hsp90 inhibitor cytotoxicity. Our findings reveal that SUMOylation is dispensable for HSF1 activation and transactivation capacity during the early phase of HSR. These results refine our understanding of HSF1 regulation and suggest that alternative strategies targeting HSF1 stability and degradation may enhance the therapeutic efficacy of proteostasis-targeting cancer therapies.